LITERATUR REVIEW: IMPLEMENTASI MODEL PEMBELAJARAN SOMATIC, AUDITORY, VISUAL, INTELLECTUAL BERBANTUAN POWERPOINT INTERAKTIF SEBAGAI KATALISATOR MOTIVASI BELAJAR IPAS DI SEKOLAH DASAR - Surya Dewi, Dika; Kurnia Wati, Ni Nyoman; Angga Dewi, Putu Yulia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to provide a comprehensive overview of the effectiveness of implementing SAVI (Somatic, Auditory, Visual, Intellectual) learning with interactive Powerpoint as a catalyst for motivation in learning Natural and Social Sciences (IPAS) in Elementary Schools. The method used is a literature review, which includes collecting, filtering, abstracting, and analyzing and synthesizing findings from previous studies and expert opinions. The results of the study indicate that the SAVI (Somatic, Auditory, Visual, Intellectual) model is able to activate students' multisensory engagement through body movement, hearing, visualization, and critical thinking processes, while interactive Powerpoint strengthens visual and auditory aspects and stimulates intellectual through animation features, relevant videos, and interactive quizzes. The integration of these two approaches consistently increases motivation, active participation, understanding of abstract concepts, and student learning outcomes. The conclusion of the study confirms that the SAVI (Somatic, Auditory, Visual, Intellectual) learning model with interactive Powerpoint is an innovative and effective approach that can be used as a reference for teachers in creating interesting and meaningful Natural and Social Sciences (IPAS) learning.